2014
DOI: 10.1371/journal.pone.0084362
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Aldosterone and the Metabolic Syndrome in Patients with Obstructive Sleep Apnea Hypopnea Syndrome: Effect of Continuous Positive Airway Pressure Treatment

Abstract: BackgroundMetabolic syndrome (MS) occurs frequently in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). We hypothesized that aldosterone levels are elevated in OSAHS and associated with the presence of MS.MethodsWe studied 66 patients with OSAHS (33 with MS and 33 without MS) and 35 controls. The occurrence of the MS was analyzed according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) clinical criteria. Measurements of plasma renin activity (PRA), aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
2
23
0
1
Order By: Relevance
“…In fact, a number of reports have suggested that primary aldosteronism may be a common cause of hypertension, with prevalence estimates ranging from 6% to 20%, whereas among patients with resistant hypertension, the prevalence ranges from 20% to 36% [45,46]. Interestingly, recent studies also implicate aldosterone in the pathogenesis of metabolic syndrome [47]. Elevated aldosterone levels seem to lead not only to sodium retention and volume expansion, but also to increased inflammation and oxidative stress, which in turn promote insulin resistance, impaired pancreatic β-cell function, endothelial dysfunction and hypertension [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a number of reports have suggested that primary aldosteronism may be a common cause of hypertension, with prevalence estimates ranging from 6% to 20%, whereas among patients with resistant hypertension, the prevalence ranges from 20% to 36% [45,46]. Interestingly, recent studies also implicate aldosterone in the pathogenesis of metabolic syndrome [47]. Elevated aldosterone levels seem to lead not only to sodium retention and volume expansion, but also to increased inflammation and oxidative stress, which in turn promote insulin resistance, impaired pancreatic β-cell function, endothelial dysfunction and hypertension [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with OSA display high levels of serum aldosterone [67] and there is a correlation between aldosterone levels and worsening of apnoea-hypopnea index (AHI) [68,69]. Aldosterone excess may play a pivotal role in the pathophysiology of OSA and, on the other hand, OSA seems to increase aldosterone levels by activation of the renin-angiotensin-aldosterone system; this excess appears to be partially reversible with continuous positive airway pressure in patients with high aldosterone level at baseline [69].…”
Section: Prevalence Of Primary Aldosteronism In Special Populationmentioning
confidence: 99%
“…The effect of aldosterone on MetSyn in other conditions has however been studied. Higher significant levels were found in MetSyn participants compared to non-MetSyn subjects among patients with obstructive sleep apnea hypopnea syndrome (OSAHS) [33]. Similarly, a cross-sectional study conducted in 356 participants from 69 families of African descent Seychelles found aldosterone to be independently associated with metabolic syndrome [34].…”
Section: Discussionmentioning
confidence: 98%